Work and Family Demands and Life Stress among Chinese Employees: The Mediating Effect of Work-Family Conflict - CHOI, Jaepil (Institutional Knowledge at Singapore Management University, 2008)
As two primary domains of adult life, work and family are known to influence life stress among employees. However, because most research in this area has been conducted in the Western setting, very little is known as to whether demands in the work and family domains are two key sources of life stress among employees in developing countries as well. We investigated life stresses of 239 Chinese employees, based on the work-family interface perspective. We found that work and family demands cause life stress among Chinese employees. Contrary to our expectations, work demands appear to have a lesser impact on life stress than family demands, although the difference is not substantial. Furthermore, while the effect of family demands on life stress is fully mediated by work-family conflict, work demands affect life stress both directly and indirectly through work-family conflict.